Anaesthesia for endovascular aneurysm repair. Issue 4 (April 2022) - Barrett, John; Jones, Sian
Abstract: The surgical management of an abdominal aortic aneurysm (AAA) can be undertaken via an open or endovascular approach. The use of an endovascular approach has benefits for the patient by being less invasive with initially lower mortality and morbidity and a shorter hospital stay, although the long-term outcomes match open techniques. The endovascular technique requires more specialist resources, including stents and imaging equipment. In the UK, endovascular techniques are usually performed in specialist hospitals with specialist teams of interventional radiologists, vascular surgeons and anaesthetists. Patients requiring endovascular repair of their AAA can present the anaesthetist with a range of complex comorbidities that require specific management and optimization preoperatively. The intraoperative management of the patient can vary, depending on patient, surgical and anaesthetic factors and from local, regional or general anaesthesia techniques. The postoperative complications are generally minimal, but patients require lifelong follow up making the procedure more expensive than an open operation.